The Influence of Organizational Communication and Job Stress on Job Satisfaction and Its Impact on Employee Performance at A Notary’s Office Abi Jumroh Harahap Rantauprapat - Ananda, Chantika Febriyani; Nasution, Ade Parlaungan; Al Ihsan, Muhammad Ali (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2022)
Offices providing legal services, and non-court mediation institutions, legal drafting of legislation are the duties of the Notary and PPAT offices, one of the best services available in Rantauprapat is the Notary Office Abi Jumroh Harahap. Carrying a good name is one of the employees’ burdens so that the office’s image remains good in the eyes of the public. Demonstrating good service and getting good results ultimately also becomes a pressure for notaries and employees. The research samples taken were employees of the Notary Office Abi Jumroh Harahap Rantauprapat, namely 50 samples. Structural Equation Model (SEM) program analysis method via Smart PLS software. The research results show that organizational communication and satisfaction have a positive and significant impact on performance but work stress does not have a significant effect on organizational performance and communication, work stress and satisfaction together have an effect on performance.